Cognitive and Emotional Empathy in Individuals with Spinal Cord Injury. (10th February 2019) - Guadagni, Veronica; Sarà, Marco; Conson, Massimiliano; Carolei, Antonio; Sacco, Simona; Vadini, Silvia; Pistarini, Caterina; Barbonetti, Arcangelo; Iaria, Giuseppe; Pistoia, Francesca
Abstract : Background . Empathy has been conceptualized as comprising a cognitive and an emotional component, the latter being further divided into direct and indirect aspects, which refer, respectively, to the explicit evaluation of the observer's feelings while attending someone in an emotional situation and to the physiological response of the observer. Empathy has been previously investigated in several neurological disorders. Objective . This study is aimed at investigating empathy in patients with spinal cord injury (SCI). We hypothesize that, due to deafferentation following their injury, SCI patients will display difficulty in the processing of emotional stimuli and blunted empathic responses as compared to healthy controls. Materials and Methods . 20 patients with spinal cord injury (SCI) (12 males and 8 females, meanage = 50.9, standard deviationSD = 16.1 years; meaneducation = 10.9, SD = 4.1 years) were included in the study and compared to 20 matched healthy subjects. Participants were investigated using the State-Trait Anxiety Inventory (Form Y) (STAI-Y), the Beck Depression Scale, and the Toronto Alexithymia Scale. Moreover, participants were further evaluated by means of the Interpersonal Reactivity Index (IRI), which explores both cognitive and emotional aspects of empathy, and through an experimental protocol based on the use of a modified version of the computerized Multifaceted Empathy Test (MET) to evaluate emotional (direct and indirect) empathy and the ability to judge the valence of complex emotional scenes. Results . As compared to healthy controls, SCI patients reported higher scores on the Perspective-Taking subscale of the IRI, while, on the modified MET, they were less accurate in identifying the valence of neutral scenes, notwithstanding their spared direct and indirect emotional empathy ability. Furthermore, we found a significant negative correlation between the time interval since injury and the direct emotional empathy scores on the positive images, as well as a negative correlation with the indirect emotional empathy scores on both positive and neutral images, indicating a blunting of the empathic responses as time elapses. Conclusion . Results suggest that SCI patients, when analyzing the meaning of emotional stimuli, tend to rely on a cognitive empathy strategy rather than on emotion simulation.